How urbanization affects CO2 emissions in Malaysia? The application of STIRPAT model - Nanthakumar, Loganathan; Khalid, Ahmed; Ahmed Taneem, Muzaffar (Elsevier Ltd, 2016)
We investigate the impact of urbanization on CO2 emissions by applying the Stochastic Impacts by Regression on Population, Affluence and Technology (STIRPAT) in the case of Malaysia over the period of 1970Q1–2011Q4. Empirically, after testing the integrating properties of the variables using the unit root test, we applied the Bayer–Hanck combined cointegration approach to examine the cointegration relationship between the variables. Further, we tested the robustness of the long-run relationship in the presence of structural breaks using ARDL bounds testing approach. The causal relationship between the variables is investigated by applying the VECM Granger causality test. Our results validate the existence of cointegration in the presence of structural breaks. The empirical results exposed that economic growth is a major contributor to CO2 emissions. Besides, energy consumption raises emissions intensity and capital stock boosts energy consumption. Trade openness leads affluence and hence increases CO2 emissions. More importantly, we find that the relationship between urbanization and CO2 emissions is U-shaped i.e. urbanization initially reduces CO2 emissions, but after a threshold level, it increases CO2 emissions. The causality analysis suggests that the urbanization Granger causes CO2 emissions.